Analisis Laporan Keuangan UMKM Berdasarkan Standar Akuntansi Keuangan Entitas Mikro Kecil Menengah (EMKM) (Studi Kasus Pada Isla Kuta Mandalika) - Mayang, Baiq Nimas Ayu Widia Gusti; Sasanti, Elin Erlina (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study aims to analyze the financial statements of Micro, Small, and Medium Enterprises (MSMEs) based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM), focusing on a case study in Isla Kuta Mandalika. MSMEs play a significant role in the national economic process; however, they often face difficulties in preparing financial statements that comply with applicable accounting standards. The implementation of SAK EMKM is expected to improve the quality of financial statements, which in turn can support better decision-making for business owners and other stakeholders. From the research findings, it is concluded that the application of SAK EMKM is crucial for enhancing the transparency and accountability of MSME financial statements. Therefore, it is recommended that relevant parties, such as the government and educational institutions, provide more intensive social training regarding SAK EMKM to MSME actors. Thus, it is hoped that MSMEs in Isla Kuta Mandalika can improve the quality of their financial statements, ultimately supporting the growth and sustainability of their businesses.